Game Utilization as a Media to Train the Balance of Left and Right Brain - Evan Wijaya (SISFORMA, 2017)
Human have two brain hemispheres, left hemisphere and right hemisphere. Left hemisphere is used for processing language, words, numbers, equations, etc. Right hemisphere is used for processing creativity, imagination, music, color, etc. Every human should have balance between left and right hemisphere. One method that could be used for balancing brain hemispheres is to use left and right hands for using tools, writing, or typing. “Typing Rhythm” is a game for PC platform, the purpose of this game is for brain balancing exercise by typing lyric of a song while the song is played.